Factors Influencing Highly Educated Adolescent In Determining The Number Of Children Desired - Anandalia Athaya Zahra; Agushybana, Farid; Mawarni, Atik; Nuridzin, Dion Zein (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: The birth rate in Indonesia has decreased from 2.41 in 2010, to 2.18 in 2020 and is predicted to keep on decreasing in the following years. If this continues, Indonesia's population will be dominated by the elderly. This research aims to find out what factors influence highly educated adolescents in determining the number of children desired. Method: This research is a quantitative study with a cross-sectional approach. The selected sample in this study was 193 adolescents, involving unmarried adolescents aged 17-24 years. Sampling was carried out using cluster sampling where samples from each cluster were divided proportionally. Data was collected using a questionnaire distributed via Google Forms Result: Multivariate analysis using multiple logistic regression found that the variables that simultaneously influence adolescents in determining the number of children are family size (p-value = 0.009) and age (p-value = 0.043) Conclusion: Variables related to determining the number of children adolescents desire are age and family size, while variables that influence the number of children adolescents desire are family size, age, and gender